Metabolomics analysis unveils important changes involved in the salt tolerance of Salicornia europaea - Duan, Huirong; Tiika, Richard John; Tian, Fuping; Lu, Yuan; Zhang, Qian; Hu, Yu; Cui, Guangxin; Yang, Hongshan (Frontiers in Plant Science, 2023)
Salicornia europaea is one of the world’s salt-tolerant plant species and is recognized as a model plant for studying the metabolism and molecular mechanisms of halophytes under salinity. To investigate the metabolic responses to salinity stress in S. europaea, this study performed a widely targeted metabolomic analysis after analyzing the physiological characteristics of plants exposed to various NaCl treatments. S. europaea exhibited excellent salt tolerance and could withstand extremely high NaCl concentrations, while lower NaCl conditions (50 and 100 mM) significantly promoted growth by increasing tissue succulence and maintaining a relatively stable K+ concentration. A total of 552 metabolites were detected, and 500 of which were differently accumulated, mainly consisting of lipids, organic acids, saccharides, alcohols, amino acids, flavonoids, phenolic acids, and alkaloids. Sucrose, glucose, p-proline, quercetin and its derivatives, and kaempferol derivatives represented core metabolites responsive to salinity stress. Glycolysis, flavone and flavonol biosynthesis and phenylpropanoid biosynthesis were considered as the most important pathways responsible for salt-stress response by increasing osmotic tolerance and antioxidant activities. The high accumulation of some saccharides, flavonoids and phenolic acids under 50 mM NaCl compared to 300 mM NaCl might contribute to the improved salt tolerance under the 50 mM NaCl treatment. Furthermore, quercetin, quercetin derivatives, and kaempferol derivatives showed varied change patterns in the roots and shoots, while coumaric, caffeic, and ferulic acids increased significantly in the roots, implying that coping strategies in the shoots and roots under salinity stress varied. These findings lay the foundation for further analysis of the mechanism underlying the response of S. europaea to salinity.